The Nature of Object of Perception and Its Role in the Knowledge Concerning the External World - Suojanen, Mika (fi=Turun yliopisto|en=University of Turku|, 2015)
Questions concerning perception are as old as the field of philosophy itself. Using the first-person perspective as a starting point and philosophical documents, the study examines the relationship between knowledge and perception. The problem is that of how one knows what one immediately perceives. The everyday belief that an object of perception is known to be a material object on grounds of perception is demonstrated as unreliable. It is possible that directly perceived sensible particulars are mind-internal images, shapes, sounds, touches, tastes and smells. According to the appearance/reality distinction, the world of perception is the apparent realm, not the real external world. However, the distinction does not necessarily refute the existence of the external world. We have a causal connection with the external world via mind-internal particulars, and therefore we have indirect knowledge about the external world through perceptual experience. The research especially concerns the reasons for George Berkeley’s claim that material things are mind-dependent ideas that really are perceived. The necessity of a perceiver’s own qualities for perceptual experience, such as mind, consciousness, and the brain, supports the causal theory of perception. Finally, it is asked why mind-internal entities are present when perceiving an object. Perception would not directly discern material objects without the presupposition of extra entities located between a perceiver and the external world. Nevertheless, the results show that perception is not sufficient to know what a perceptual object is, and that the existence of appearances is necessary to know that the external world is being perceived. However, the impossibility of matter does not follow from Berkeley’s theory. The main result of the research is that singular knowledge claims about the external world never refer directly and immediately to the objects of the external world. A perceiver’s own qualities affect how perceptual objects appear in a perceptual situation.

Havaintoon liittyvät ongelmat ovat kuuluneet filosofiaan tämän alusta asti. Käyttäen henkilön omakohtaista havaintotilannetta lähtökohtana ja filosofista aineistoa, tutkimus käsittelee tiedon ja havainnon suhdetta. Tutkimusongelmana on, miten tietää, mitä havaitsee parhaillaan. Arkielämän uskomus, että havainnon perusteella tiedetään havainnon kohde materiaaliseksi objektiksi, tullaan osoittamaan epäluotettavaksi. On mahdollista, että yksilöt, jotka havaitaan välittömästi, ovat mielensisäisiä kuvia, muotoja, ääniä, tuntemuksia, makuja ja tuoksuja. Näennäisyys/todellisuus erottelun mukaan havaintomaailma on näennäinen eikä todellinen, mielestä riippumaton ulkomaailma. Kuitenkaan erottelu ei välttämättä kiellä ulkomaailman olemassa oloa, vaan mielensisäisten yksilöiden kautta olemme yhteydessä ulkomaailmaan. Siis meillä on tietoa epäsuorasti ulkomaailmasta havaintokokemuksen kautta. Tutkimus keskittyy erityisesti George Berkeleyn väitteen perusteisiin, että materiaaliset objektit ovat mielensisäisiä ideoita, ja juuri nämä havaitaan suoraan. Henkilön ominaisuuksien kuten mielen, tietoisuuden ja aivojen välttämättömyys havaintokokemukselle tukee havainnon kausaalista teoriaa. Lopuksi tutkimuksessa kysytään perusteita, miksi havainnossa on mielensisäisiä entiteettejä. Havainto ei tavoittaisi suoraan materiaalista objektia ilman oletusta havaitsijan ja ulkomaailman välissä olevista lisäentiteeteistä. Tutkimuksen tulokset kuitenkin esittävät, että havainto ei ole riittävä syy tietää, mikä havaintoilmentymä on ja että tällaisten havaintoilmentymien olemassaolo on välttämätöntä, jotta tietää havaitsevansa ulkomaailman. Kuitenkaan Berkeleyn teoriasta ei seuraa aineen mahdottomuus. Tutkimuksen päätulos on, että yksittäiset tietoväitteet ulkomaailmasta eivät ole koskaan suoraan ja välittömästi ulkomaailman kohteista. Havaitsijan omat ominaisuudet vaikuttavat, millaisina havaittavat objektit ilmenevät havaintotilanteessa.